PENGEMBANGAN BUKU AJAR TEMATIK TERPADU BERBASIS PROBLEM BASED LEARNING DI KELAS V SD: The Development Of Integreted Thematic Book Using Problem Based Learning For 5 Grade Student In Primary School - M. Anggrayni; Lika Apreasta (Cerdas Proklamator, 2022)
Text book is the important component in learning process, it is caused by the content of the text book will be delivered to the students in learning process. Recently, found that the teachers do not develop the textbook which is based on thematic integrated. In teaching the teachers are still be guided by teachers’ and students’ handbooks which are provided by Kemendikbud. There are some weakness in the teachers’ and students’ handbook that used in learning process, and need development. Based on the problem above, the researcher wants to develop the textbook of thematic integrated based on Problem Based Learning. The purpose of this research is to develop the textbook thematic integrated based on Problem Based Learning for fifth grade. The validity, practicallity, and efectiveness of this thematic integrated book for the fifth grade. This research used Four-D model. The subject of this research were teacher and fifth grade students in SDN Percobaan Padang and SDN 05 Padang Pasir. The technique of data analysis was analysis of validity,practicality and effectiveness. The data of validity obtained from the validity of textbook. The practicallity observed from the learning, questionaire of teachers’ response, questionaire of students’ response, and interview. The effectiveness conducted from observation of activity and the learning outcome of the students. The result of this research were: in definition stage it produced curriculum analysis, needs and students. The cover, acknowledgement, the book guidance, standard of competence and core competence, table of content, chapters and stabdard competence mapping, sub chapters, indicators, purposes of the learning and the steps of Problem Based Learning were the result of textbook design stage. The development stage for the average validity was 3.81 which is valid. The practicality of this research in learning process was 94%, the questionaire of teachers’ respond was 86.11% and for the questionaire of students’ response was 90% and they are included to very practicallity. The disseminate stage for the effectiveness was 87.81% for the percentage of the students. Generally, The learning outcomes of the students was very good. The conclusion was the textbook based on Problem Based Leaning which is thematc integrated and developed had been valid, pracitcal, and effective to use as one of textbook for teaching in fifth grade in elementary school.